The Effect of Organizational Learning on Improving Hard Skills, Soft Skills, and Innovation on Performance - Mulyadi Mulyadi; Wellty Mely Betesda Br Sinaga; Dwi Nirwana; Renova Manulang (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: This study sought to quantify how hard skills, soft skills, organization learning, and innovation capability all affected performance. Background Problems: The abilities required to advance in the workplace are changing due to the expanding workplace. Every university graduate is expected to perform exceedingly well, possess high levels of competence, and be adept at their jobs. Educational institutions play a crucial role in developing competent graduates with hard skills, soft skills, and self-efficacy. Novelty: This study evaluates the similarities and differences between the previous research and the research conducted because the earlier research did not integrate the three variables in one research title. Research Methods: This study employs a qualitative literature study. Secondary data is gathered from research findings from multiple references that are pertinent to the study's subject and goals. Finding/Results: The findings demonstrated that organizational learning, hard and soft skills, and innovation capability all had a direct, positive, and significant impact on performance. Additionally, among other factors, soft skills have the most significant an impact on performance. Conclusion: Every educational institution must continue to focus on developing hard and soft skills through training to improve employee performance.